From Silent Thinkers to Active WRITERS: AI Chatbots in EFL Idea Expression - Jarbowah, Angel; Retnowati, Nanik; Nuraeni, Nuraeni (UICELE, 2026)
The growing presence of artificial intelligence in education has opened new possibilities for supporting English as a Foreign Language (EFL) writing, yet the specific role of AI chatbots in helping students express ideas remains underexplored. This study investigates how AI chatbots such as ChatGPT, Gemini, and Claude support idea expression among EFL university students, addressing the phenomenon of “silent thinkers” who learners rich in ideas but unable to translate them into written form. Using a mixed-methods design, primarily qualitative and supported by quantitative data, 30 EFL university students completed a Google Form questionnaire comprising 19 Likert-scale items and 6 open-ended questions. Quantitative data were analyzed descriptively, and qualitative data were analyzed thematically following Braun and Clarke’s framework. Findings, interpreted through Vygotsky’s Sociocultural Theory and Krashen’s Affective Filter Hypothesis, reveal that AI chatbots function as scaffolding tools that support brainstorming, idea generation, vocabulary access, and sentence construction, while also reducing writing anxiety and increasing confidence and engagement. Students nonetheless expressed concern about overdependence, plagiarism, and inaccurate AI output, and emphasized the necessity of teacher guidance. The study concludes that AI chatbots, used responsibly, can transform silent thinkers into active writers.